Disasters in the United States Frequency, Costs, and Compensation - Vroman, Wayne (W.E. Upjohn Institute, 2016)
This book focuses on three disaster-related categories: major disaster declarations, emergency declarations, and fire management assistance declarations. The authors utilize these official definitions to draw inferences about the frequency, geographic patterns, trends, and financial costs related to disasters.